2017
DOI: 10.3892/ol.2017.6952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment psoas muscle mass on survival for patients with unresectable pancreatic cancer undergoing systemic chemotherapy

Abstract: Abstract. To the best of our knowledge, there are few previous studies that have investigated the effect of decreased skeletal muscle mass (DSMM) on survival in patients with unresectable advanced pancreatic cancer (APC) who are undergoing systemic chemotherapy. Thus, the present study aimed to investigate the impact of DSMM, as determined by the psoas muscle index (PMI) following computed tomography and prior to systemic chemotherapy, on the outcomes of patients with unresectable APC (n=61). The primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
1
18
2
2
Order By: Relevance
“…PMI, which is a measure of muscle mass, was an independent prognostic factor in palliative care patients. PMI measurement has been widely used as an alternative method for evaluating all major skeletal muscles at the lumbar level, and PMI has been associated with prognosis in patients with cancer [22,23] and with surgical outcomes [24]. However, the previous studies have examined patients receiving anticancer therapy with a prognosis of more than several months.…”
Section: Discussionmentioning
confidence: 99%
“…PMI, which is a measure of muscle mass, was an independent prognostic factor in palliative care patients. PMI measurement has been widely used as an alternative method for evaluating all major skeletal muscles at the lumbar level, and PMI has been associated with prognosis in patients with cancer [22,23] and with surgical outcomes [24]. However, the previous studies have examined patients receiving anticancer therapy with a prognosis of more than several months.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we evaluated the reproducibility of the proposed model in the subsequent Vs (n=75), which included patients in the other hospital (Takarazuka municipal hospital). (Figure 1) Clinical data in the Ts were examined retrospectively and the constructed model was also verified in a retrospective manner for the independent Vs. Psoas muscle index (PMI) for the assessment of muscle mass was measured using CT as reported elsewhere [30].…”
Section: Our Study Planmentioning
confidence: 99%
“…Standard therapies such as surgical resection and systemic chemotherapy will be chosen based on tumour status and baseline characteristics in each patient after thorough discussion with surgeons and oncologists. 20 27 …”
Section: Study Protocolmentioning
confidence: 99%
“… 18 19 In our previous investigation, we demonstrated that decreased skeletal muscle mass could be a significant predictor of prognosis in patients with unresectable advanced PC undergoing systemic chemotherapy, and some interventions for patients with sarcopenic PC could be beneficial for ameliorating clinical outcomes. 20 …”
Section: Introductionmentioning
confidence: 99%